Therapeutic benefits of nitric oxide in lung transplantation - Dugbartey, G.J. (Biomedicine & Pharmacotherapy, 2023)
Lung transplantation is an evolutionary procedure from its experimental origin in the twentieth century and is now recognized as an established and routine life-saving intervention for a variety of end-stage pulmonary diseases refractory to medical management. Despite the success and continuous refinement in lung trans plantation techniques, the widespread application of this important life-saving intervention is severely hampered by poor allograft quality offered from donors-after-brain-death. This has necessitated the use of lung allografts from donors-after-cardiac-death (DCD) as an additional source to expand the pool of donor lungs. Remarkably, the lung exhibits unique properties that may make it ideally suitable for DCD lung transplantation. However, primary graft dysfunction (PGD), allograft rejection and other post-transplant complications arising from un avoidable ischemia-reperfusion injury (IRI) of transplanted lungs, increase morbidity and mortality of lung transplant recipients annually. In the light of this, nitric oxide (NO), a selective pulmonary vasodilator, has been identified as a suitable agent that attenuates lung IRI and prevents PGD when administered directly to lung donors prior to donor lung procurement, or to recipients during and after transplantation, or administered indirectly by supplementing lung preservation solutions. This review presents a historical account of clinical lung transplantation and discusses the lung as an ideal organ for DCD. Next, the author highlights IRI and its clinical effects in lung transplantation. Finally, the author discusses preservation solutions suitable for lung trans plantation, and the protective effects and mechanisms of NO in experimental and clinical lung transplantat
Research Article
Keywords: Lung transplantation; Primary graft dysfunction (PGD); Lung allograft rejection, nitric oxide (NO)